A good learning opportunity, but is it for me? A study of Swedish students' attitudes towards exchange studies in higher education. (August 2014) - Ahn, Song-ee
This article describes students' involvement and interest in exchange programmes in Swedish higher education. Law and Engineering bachelor's programmes were chosen to exemplify an over-represented and under-represented group respectively in terms of international mobility in this context. The study combines interview and survey data. The author argues that the different institutional practices in educational programmes impact on students' experienced involvement in exchange studies.